2023
DOI: 10.3390/mi14071436
|View full text |Cite
|
Sign up to set email alerts
|

Superelastic NiTi Functional Components by High-Precision Laser Powder Bed Fusion Process: The Critical Roles of Energy Density and Minimal Feature Size

Abstract: Additive manufacturing (AM) was recently developed for building intricate devices in many fields. Especially for laser powder bed fusion (LPBF), its high-precision manufacturing capability and adjustable process parameters are involved in tailoring the performance of functional components. NiTi is well-known as smart material utilized widely in biomedical fields thanks to its unique superelastic and shape-memory performance. However, the properties of NiTi are extremely sensitive to material microstructure, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The design of laser additive manufacturing covered in this Special Issue includes the material design (e.g., the high reflectivity and thermal conductivity multi-material 3D printing [ 22 ] and the microalloying for LPBF [ 20 ]) and the structural design (e.g., the triply periodic minimal-surface (TPMS) structure [ 18 ], the thin-walled main support structure [ 23 ]).…”
Section: Design Of Laser Additive Manufacturing In Special Issuementioning
confidence: 99%
See 2 more Smart Citations
“…The design of laser additive manufacturing covered in this Special Issue includes the material design (e.g., the high reflectivity and thermal conductivity multi-material 3D printing [ 22 ] and the microalloying for LPBF [ 20 ]) and the structural design (e.g., the triply periodic minimal-surface (TPMS) structure [ 18 ], the thin-walled main support structure [ 23 ]).…”
Section: Design Of Laser Additive Manufacturing In Special Issuementioning
confidence: 99%
“…For the TPMS structure high-precision fabrication, Qu et al [ 18 ] reported the critical roles of energy density and minimal feature size on superelastic NiTi functional components by high-precision LPBF. In this work, extensive parameter studies were conducted to reveal their influences on the microstructure and mechanical properties of as-printed components with different minimal feature sizes (thin wall structure, bulk samples, TPMS structures, etc.).…”
Section: Design Of Laser Additive Manufacturing In Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, LPBF also has great potential for the manufacturing of gradient materials. For example, Song et al [ 12 ] proposes an analytical approach to design stretching-dominated truss lattices with tailored elastic properties, including isotropic elasticity, tailored zero/negative Poisson’s ratios, tailored Young’s moduli ratios along specified directions, and the prototype was prepared using the Micro-LPBF technique, these techniques could be used to develop new engineering applications and promote the development of NiTi SMAs [ 13 , 14 , 15 ]. Therefore, the NiTi SMAs fabricated by LPBF have become a major topic in the research community recently [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dadbakhsh et al [ 22 ] investigated the anisotropy of LPBFed NiTi SMAs (with different building directions) and clarified that the crystallographic textures have an important effect on the mechanical properties of LPBFed NiTi SMAs. Gu et al [ 15 ] optimized the process parameters of LPBFed NiTi, an excellent shape recovery rate of 88.23% was achieved under the optimal parameters, and a shape-recovery rate of 96.7% was achieved under electrical actuation for a structure with a pre-compressed strain of 20%. Shi et al [ 19 ] investigated the effects of crystallographic anisotropy on the microstructure, phase transformation and the tribological properties of NiTi shape memory alloys fabricated by LPBF and revealed how different LPBF-induced microstructures affect mechanical properties and wear properties.…”
Section: Introductionmentioning
confidence: 99%